A avaliação da qualidade de vida como indicadora para a condução de grupos de promoção da saúde para idosos na comunidade - Paula, Gabriella Ribeiro de (2014)
Group activities have shown to be useful and efficient to educational interventions and health promotion in health care in general, especially in basic care. Strategy recommended in several programs of the Brazilian Health Ministry, group work still lacks instruments of assessment of its outcomes. Thus, this study aimed at analyzing the use of assessment of quality of life (QL) as a guide to manage groups of health promotion in the community. This is a cross-sectional, quantitative, descriptive research study carried out in the municipality of Goiânia, Goiás, from 2012 to 2013, with 46 elderly people aged over 60 years who participated in two groups (G1 and G2) of health promotion in the community. The participants were interviewed individually in their home or places previously consented for filling and collecting data: sociodemographic questionnaire, WHOQOL-BREF and WHOQOL-OLD. Data was typed and submitted to descriptive analysis in the SPSS Software. 26 elderly (G1) and 20 elderly (G2) participated in this study, mostly female ( 84.6% and 90.0%, respectively) , under the age of 80 (76.9% and 90.0% , respectively). The majority were retired (78.3%), with individual income of up to the Brazilian minimum wage. In the G1, 65.2% of the elderly had up to 4 years of education, whereas in the G2, 80.0% reported having over 4 years of education. In absolute numbers, the highest score achieved by the participants in G1 in the WHOQOL-BREF was regarding the dominium “Social Relations” (75.32), and the lowest in the dominium regarding “Environment” (60.22), whereas in G2, the highest score was in the dominium “Psychologic”(69.25) and the lowest score also regarding the dominium “Environment” (61.56). Highest average scores in absolute numbers achieved in WHOQOL-OLD were reached on facets “ Social Participation”(72.36) by G1, and “Past, Present and Future Activities”(69.25) by G2, whereas the facet “Death and Dying” had the lowest scores (56.73 and 44.06, respectively). The assessment of QL in the elderly was valuable to identify the level of satisfaction of this population with different aspects influencing their well-being and health, allowing coordinators of groups for the elderly to identify the needs of the participants, and then, plan activities more suitable to manage groups of health promotion for the elderly, so that they could contribute to better their lives in general. .